A Simple Method for Generating Narrowly-dispersed Bioaerosols in Various Sizes - Young-Su Jeong; Hyunsoo Seo; Sang-Soo Han; Young-Jin Koh; Kibong Choi (Aerosol and Air Quality Research)
Abstract Biological warfare agents (BWAs) cause disease in humans, animals, and plants when purposefully dispersed in an area. To minimize contamination and personnel exposure and initiate early treatment, effective BWA detection or monitoring techniques are needed. Currently, bioaerosol detection or monitoring techniques are used for detecting BWA; however, these techniques have limitations, such as limited sensitivity. To improve the detection performance and develop novel techniques, an additional step in sample preparation, such as obtaining particles of various sizes, is needed. In this study, we investigated the simple and effective generation of bioaerosol particles using a custom-made inkjet aerosol generator (IJAG). Unlike previous inkjet aerosol generators, the operation conditions of the IJAG are fixed at a nozzle heating temperature of 140°C, a driver voltage of 150 V, a pulse width of 60 µs, and a frequency of 250 Hz. The only controlled factor was the concentration of bioaerosol models, including Bacillus globigii spores, ovalbumin, and polystyrene sphere latex. Our system generated bioaerosols with a diameter of 1–8 µm and a narrow distribution size. These results suggest that our IJAG system can achieve the simple and versatile generation of narrow-dispersed bioaerosols for a wide range of available materials. Our study can help improve the sensitivity of detection and monitoring systems for BWAs and bioaerosols.